UV response on dielectric properties of nano nematic liquid crystal - Kamal Kumar Pandey; Pankaj Kumar Tripathi; Abhishek Kumar Misra; Rajiv Manohar (Results in Physics, 2018)
In this work, we investigate the effect of UV light irradiation on the dielectric parameters of nematic liquid crystal (5CB) and ZnO nanoparticles dispersed liquid crystal. With addition of nanoparticles in nematic LC are promising new materials for a variety of application in energy harvesting, displays and photonics including the liquid crystal laser. To realize many applications, however we optimize the properties of liquid crystal and understand how the UV light irradiation interact the nanoparticles and LC molecules in dispersed/doped LC. The dielectric permittivity and loss factor have discussed the pure nematic LC and dispersed/doped system after, during and before UV light exposure. The dielectric relaxation spectroscopy was carried out in the frequency range 100 Hz–10 MHz in the nematic mesophase range. Keywords: Dielectric permittivity, Relaxation frequency, Nematic liquid crystal, UV light irradiation